In situ imaging of microplastics in living organisms based on mass spectrometry technology - Ye Li; Xiaoyu Sha; Yuan Wang; Yanfang Zhao; Junjie Zhang; Ping Wang; Xiangfeng Chen; Baoshan Xing; Lei Wang (Eco-Environment & Health)
Plastic pollution is widely present in terrestrial and aquatic ecosystems, and microplastics (MPs) can be detected in organisms. In situ detection methods for MPs in organisms have attracted widespread attention. Traditional imaging characterization methods of MPs, including stereo microscopes and fluorescence microscopy, are typically used to image artificially added microsphere standards under laboratory conditions. However, they cannot specifically identify MPs in biological samples. Thus, there is a need for a detection technique that can provide spatial distribution information of MPs in biological samples as well as measure their quality and quantity. In this perspective, to obtain high-resolution images with chemical composition analysis, we compared ion sources for ionizing plastic macromolecules and mass analyzers for analyzing macromolecules. Matrix-assisted laser desorption/ionization (MALDI) is suitable for imaging characterization, while time-of-flight (TOF) and Orbitrap mass spectrometry are suitable for polymer mass spectrometry analysis. Furthermore, we propose a technique that combines MALDI with TOF or Orbitrap, which holds promise for the in situ imaging of MPs in biological samples.